The greatest game ever played [videorecording (DVD)] - Paxton, Bill; LaBeouf, Shia, 1986-; Dillane, Stephen, 1956-; Frost, Mark, 1953- (Walt Disney Home Entertainment, 2006)
Based on the 1913 U.S. Open golf championship-at which two equally sympathetic young men, both of whom grew up economically and socially disadvantaged, go club to club in one of the most exciting and dramatic athletic events of the 20th century.